The impact of statin-ezetimibe combination therapy versus statin monotherapy on coronary plaque regression in patients with acute coronary syndrome: a meta-analysis - Yusra Pintaningrum; Ketut Angga Aditya Putra Pramana (Journal of the Pakistan Medical Association, 2024)
Objective: To investigate the effects of statin monotherapy and statin-ezetimibe combination therapy on coronary plaque regression in acute coronary syndrome patients. Methods: The systematic review was conducted from July to September 2022 and comprised search on PubMed, ScienceDirect and Cochrane databases to identify studies from January 2010 to July 2022 assessing the effects of statin-ezetimibe combination therapy versus statin monotherapy on coronary plaque regression in patients with acute coronary syndrome. The outcomes of interest were total atheroma volume, plaque volume, and percent atheroma volume assessed by intravascular ultrasound. Meta-analyses were performed on the studies, and mean differences with 95% confidence interval were estimated using Review Manager v5.4. Results: Of the 730 studies identified, 12(1.64%) were shortlisted, and, of them, 5(41.7%) were analysed in detail. There were a total of 557 patients with a mean follow-up of 9 ± 2.43 months. The difference between baseline and follow-up showed significant lowering in total atheroma volume, plaque volume, and percent atheroma volume (p<0.05) in the patients who were receiving statin-ezetimibe combination therapy. Conclusion: Adding ezetimibe to statin medication was found to be significantly more successful in reducing coronary plaque than statin monotherapy. Key Words: Ezetimibe, Plaque, Atherosclerotic, Hydroxy, Coronary, Ultrasonography, Interventional.